The demand for money by private firms in a regulated economy: Theoretical underpinnings and empirical evidence for Germany 1960-1998 - Martin T. Bohl; Friedrich L. Sell (Universität der Bundeswehr München, Fachgruppe für Volkswirtschaftslehre, 2002)
Based on a cash-in-advance approach, this paper investigates theoretically the determinants of money holdings of firms under the conditions of a highly regulated labor market and analyses empirically the demand for money of German businesses during the period 1960-1998. As a result of our theoretical analysis the demand for cash balances by firms for shadow market activities depends among other things positively on the expected wage wedge. The empirical results show that the coefficient of the wage wegde has a positive sign in the long-run cointegrating relationship and is statistically significant positive in the short-run dynamics of the error correction model. – – Auf der Grundlage eines Cash-in-advance-Ansatzes untersucht der vorliegende Beitrag die Bestimmungsgründe der Geldnachfrage von deutschen Unternehmen (1960-1998) - vor dem Hintergrund eines hoch regulierten Arbeitsmarktes. Das theoretische Modell ergibt, daß Unternehmen Kasse für Aktivitäten auf dem Markt für Schwarzarbeit unterhalten und zwar um so mehr, je größer die Kluft zwischen den Bruttoarbeitskosten und den Nettolöhnen (wage wedge) ist. Der Koeffizient der wage wedge weist ein positives Vorzeichen in der Kointegrationsbeziehung auf und ist statistisch signifikant positiv in der kurzfristigen Dynamik des Fehler-Korrektur-Modells.
Keywords: E41; C22; J30; 330; Money Demand by Firms; Wage Wedge; Cash-in-Advance Model; Cointegration; Error-Correction; Geldnachfrage von Unternehmen; Cash-in-advance-Modell; Kointegration; FehlerKorrektur-Modell; Lohnzusatzkosten; Geldnachfrage; Cash-in-Advance-Modell; Betriebliche Liquidität; Theorie der Unternehmung; Arbeitskosten; Arbeitsmarktflexibilisierung; Schwarzarbeit; Schätzung; Deutschland